THEORETICAL AND COMPUTATIONALSTUDY OF SURFACE PHONON-POLARITON MODES ON NEW GIANTDIELECTRIC MATERIALCaCu3Ti4012 UNDER EXTRINSIC-LORENTZ OSCILLATOR MODEL - , Isom Hilmia , Kamsul Abrahaa ([Yogyakarta] : Fak. Teknik UGM, 2008)
Abstract. A theoretical and computational study of surface phonon-polariton modes on new giant dielectric material CaCu3Ti4012 under extrinsic-oscillator model has been done. We assume that the large observed static dielectric response arises from. extrinsic mechanisms, such as contributed by point, line, or .planar defects, or more generally, from sample microstructure morphology, or boundary layers, although we cannot barely abandon the corresponding intrinsic mechanism that may also cause the aforementioned phenomena. For doing so, we therefore suggest to take into account some compelling contribution from the Lorentz oscillators in the context of the extrinsic model dielectric constant arising from the microstructures of the material. The computed ATR (Attenuated Total Reflection) spectra show that the s...rface phonon-polaritons can be detected optimally at various distances between the silicon prism and the sample using the Otto configuration for each morphology. The silicon prism is used in this ATR calculation because it is transparent in the far-infrared spectral region where the resonant frequencies of the polaritons lie. Each morphology has distinct frequency regions showing the existence of surface phonon-polaritons on CaCu3Ti4012.